Verification of miRNAs in ginseng decoction by high-throughput sequencing and quantitative real-time PCR. Issue 4 (April 2019) - Wang, Yingfang; Peng, Mengyuan; Wang, Wenjuan; Chen, Yanlin; He, Zhihua; Cao, Jingjing; Lin, Zhiyun; Yang, Zemin; Gong, Mengjuan; Yin, Yongqin
Abstract: Panax ginseng C. A. Meyer is a precious traditional Chinese medicine that has been clinically used for over thousands of years. In general, ginseng needs to be prepared to ginseng decoction before taking it. MicroRNAs are a class of small (18–24 nt), single-stranded molecules that regulate gene expression at the post-transcriptional level. Considering that ginseng miRNAs may be bioactive compounds, we used Illumina high-throughput sequencing and quantitative real-time PCR (qRT-PCR) to validate the existence of miRNAs in fresh ginseng decoction which have been boiled at high temperature. Our previous studies have demonstrated that there are several miRNAs in fresh ginseng. The roots of fresh Panax ginseng were prepared according to routine methods, from which miRNAs were extracted and sequenced. A total of 43 miRNAs were identified from water decoction by Illumina high-throughput sequencing, belonging to 71 miRNA families. The target genes of these miRNAs were predicted by sequencing, and were annotated by GO, KEGG and Nr databases. The functions of these target genes mainly included plant hormone signal transduction, transcription regulation, macromolecular metabolism and auxin signaling. Nine highly expressed miRNAs (miR159, miR167, miR396, miR166, miR168, miR156, miR165, miR162 and miR394) were verified by qRT-PCR, and the results of Illumina high-throughput sequencing and qRT-PCR were consistent. Results from this study indicate that miRNAs remained stable in P. ginseng after high-temperature boiling. Additionally, Illumina high-throughput sequencing was superior in the acquisition of higher amount of small RNAs.